REVIEW: MOLECULARLY IMPRINTED-SOLID PHASE EXTRACTION (MI-SPE) DALAM ANALISIS KONTAMINAN PANGAN - SAQILA ALIFA RAMADHAN; Riezki Amalia (Farmaka, 2019)
ABSTRAKKontaminasi dalam bahan pangan dapat menyebabkan terjadinya peristiwa keracunan. Beberapa metode telah dikembangkan untuk preparasi dan analisis kandungan suatu kontaminan dalam bahan pangan. Metode yang umum digunakan dalam preparasi bahan pangan adalah Solid Phase Extraction (SPE). Untuk meningkatkan selektivitas SPE dalam pemurnian sampel, maka digunakan penerapan teknik Molecularly Imprinted Polymer (MIP) dalam sorben SPE. Review ini membahas beberapa aplikasi dari Molecularly Imprinted-Solid Phase Extraction (MI-SPE) dalam analisis kontaminan pangan. Berdasarkan hasil review, MI-SPE dapat digunakan untuk ekstraksi kontaminan pangan seperti akrilamid, bisfenol, melamin, organofosfat, fenarimol, triazin, okratoksin A, ampisilin, tetrasiklin, fluoroquinolon, dan kloramfenikol.Kata Kunci : Pangan, Solid Phase Extraction (SPE), Molecularly Imprinted Polymer (MIP), Molecularly Imprinted-Solid Phase Extraction (MI-SPE) ABSTRACTContamination in food can cause poisoning incident. Several methods have been developed for the preparation and analysis of contaminants in food. The method commonly used in food preparation is Solid Phase Extraction (SPE). To increase the SPE's selectivity in sample purification, the application of Molecularly Imprinted Polymer (MIP) technique in SPE's sorbent was used.  This review discussed several applications of Molecularly Imprinted-Solid Phase Extraction (MI-SPE) in food's contaminants analysis. Based on the review, MI-SPE can be used to purify contaminants in food like acrylamide, bisphenol, melamine, organophosphate, fenarimol, triazine, ochratoxin A, ampicillin, tetracycline, fluoroquinolone, and chloramphenicol.Keywords: Food's contaminants, Solid Phase Extraction (SPE), Molecularly Imprinted Polymer (MIP), Molecularly Imprinted-Solid Phase Extraction (MI-SPE)